A Survey of Current Procedural Practices of Australian and New Zealand Nephrologists. Issue 6 (5th March 2013) - Ritchie, Angus G.; Saunders, John; Baer, Richard; May, Stephen; ,
Abstract The aim of this study was to describe the range and extent of current procedural practices of Nephrologists and trainees in Australia and New Zealand with a specific focus on renal biopsy. A web‐based survey was constructed based on a 2009 pilot survey conducted by the authors. The survey was distributed by email. A total of 118 responses were received from 60 centers, including six pediatric centers; Nephrologists or trainees performed the following procedures: urine microscopy 36.4%; diagnostic ultrasound 10.2%; renal biopsy 93.2%; simple vascath insertion 64.4%; cuffed vascath insertion 22%; peritoneal catheter insertion 16.9%; fistula ultrasound 20.3%; and fistulography 5%. Trainees performed most renal biopsies (67.8% of respondents) and real‐time ultrasound was the commonest technique (97%). The majority of respondents believe that renal biopsy is an essential skill for trainees (78.8%); 10–25 biopsies are required for trainee proficiency (59.3%); an online training module would assist in teaching renal biopsies (67.8%). Cuffed catheter insertion and fistulography were more often performed in nonmetropolitan than in metropolitan centers. Procedures are part of Australian and New Zealand Nephrology, including specialized procedures in a minority of centers. Vascular access procedures are more common in nonmetropolitan centers. Renal biopsy is an important skill, considered essential for trainees by most.